The Distribution System of Joint Property in Polygamous Families from the Perspective of Islamic Law Compilation and Civil Code - Desy Triyana (Green Publisher Indonesia, 2025)
This research discusses the Distribution System of Joint Property in Polygamous Families from the Perspective of the Islamic Law Compilation and the Civil Code. In this context, polygamy refers to the practice of a man marrying more than one wife simultaneously. This practice is still permitted in some countries, including Indonesia, although debates about its impacts and consequences continue. One of the recurring issues in polygamous families is the division of joint property or joint assets. Based on this background, the author raises the problem formulation: How is the regulation of joint property for polygamous families according to the Islamic Law Compilation and the Civil Code. How is the distribution system of joint property to wives in polygamy according to the Islamic Law Compilation and the Civil Code. This research is a normative legal study using a statutory approach, a case approach, and a conceptual approach. Data collection is conducted through literature study with both primary and secondary legal materials. The existing legal materials are then examined and analyzed using the approaches employed in this study to address the legal issues raised. Based on the results of this research, the regulation of joint property for Muslims is governed by Law No. 1 of 1974 on Marriage and the Islamic Law Compilation, specifically Article 65 Paragraph (1) and Article 94 Paragraph (1). For non-Muslims, it is regulated by the Civil Code, specifically Article 128.